Peningkatan Kemampuan Berhitung Melalui Metode Jarimatika pada Pembelajaran Matematika di SD - Marianah Marianah; Dewi Sartika (Jurnal Inovasi Pendidikan Dasar dan Menengah, 2025)
This study aims to improve the numeracy skills of third-grade students of Mangga Besar 01 Pagi Elementary School, West Jakarta, using the Jarimatika method. The underlying problem of this study is the low ability of students in basic arithmetic operations, especially addition and subtraction, so that it requires a more effective and enjoyable learning strategy. The subjects of the study were third-grade students of Mangga Besar 01 Pagi Elementary School, West Jakarta, in the 2025/2026 academic year. This type of research is classroom action research (CAR) with a qualitative approach that was carried out in two cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. The subjects were 25 third-grade students. Data were collected through observation, interviews, and documentation, then analyzed descriptively qualitatively. The results of the study indicate that the application of the Jarimatika method can improve students' numeracy skills, especially in addition and subtraction operations. Students become more active, enthusiastic, and confident in solving math problems. In addition, the learning atmosphere becomes more fun and interactive because students can understand the concept of counting with the help of their fingers in a concrete way. Based on these results, it can be concluded that the Jarimatika method is effective as an alternative learning method to improve elementary school students' arithmetic skills.